The influence of capital structure on the financial performance of the Insurance Industry of Ghana - Atta-Doku, Francis (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration,